Evaluation of Surgical Risks and Challenges in Mandibular Third Molar Extraction Using Cone Beam Computed Tomography: A Cross-Sectional Study - Rameshwar G. Chatgile; Ajay R. Bhoosreddy; Chetan J. Bhadage (Wolters Kluwer Medknow Publications, 2024)
This study examined the association between lingual plate thickness and complications in third lower molar extraction. Cone beam computed tomography (CBCT) was used to measure the lingual plate thickness and examine its correlation with impact classification in winter. Material/Methods: A total of 183 cone beam images of the third impacted molar in the mandible were retrospectively analyzed. The impaction type of the tooth and the thickness of the lingual plate at the apex and midroot were evaluated using SIDEXIS software. Categorical variables were statistically analyzed using the Chi-square test. Results: The lingual plate thickness averaged 1.24 mm at the midroot and 1.14 mm at the apex. The study revealed a significant correlation between horizontally impacted third molars and thinner lingual plates at the midroot level (P value = 0.002). Conclusion: In third lower molars, the study showed a high correlation between the kind of impaction and the thickness of the lingual plate. Surgeons should exercise caution during extraction due to the potential risk of lingual plate fractures and emphasize the importance of preoperative CBCT planning in affected third-molar cases.